A comparative study on pesticide residue profiles in locally grown rice from conventional and sustainable agricultural methods - Indra Purnama; Farag M. Malhat; Anisa Mutamima; Fikratul Ihsan; Amalia (Jurnal Ilmiah Pertanian, 2023)
Amid escalating concerns about pesticide residues in agricultural product, this study conducts a meticulous comparative analysis of pesticide residue profiles in locally grown rice, aiming to contribute essential insights for informed decision-making in agriculture. The overarching problem addressed involves identifying pesticides in rice from conventional and sustainable farming and understanding their potential environmental and health implications on food safety. Utilizing HPLC/MS-MS, the research discerns a notable absence of over 500 pesticide types in rice cultivated according to good agricultural practices (GAP). Conversely, rice from fields deviating from GAP guidelines reveals the presence of 7 pesticide active ingredients, with 2 exceeding globally established residue limits by twice the recommended amount. Notably, bifenthrin and tebuconazole, uncommonly used in the last one years, are identified. This study underscores the urgency of adhering to sustainable agricultural practices for the safety and quality of rice, offering critical insights for future research. It not only contributes to current knowledge but also emphasizes the global necessity of safe agricultural practices to safeguard our food supply.